Perceptions of therapeutic principles in a therapeutic community - Capone, Georgina; Braham, Louise; Schroder, Thomas; Moghaddam, Nima (Emerald, 2017)
Purpose: This study aimed to explore staff and service users’ perceptions of therapeutic principles within a unique male high secure learning disability therapeutic community (LDTC). Design/methodology/approach: A qualitative approach was adopted using deductive content analysis and inductive thematic analysis. Twelve participants took part in a semi-structured interview to explore their perceptions of Haigh’s (2013) quintessence principles and any further additional therapeutic features in the environment not captured by the theory. Findings: All five quintessence principles were identified in the LDTC environment. Some limits to the principle of ‘agency’ were highlighted, with specific reference to difficulties implementing a flattened hierarchy in a forensic setting. Additional therapeutic features were identified including; security and risk, responsivity, and more physical freedom which appear to aid implementation of the quintessence principles. Research limitations/implications: The study was performed within a single case study design. Therefore results remain specific to this LDTC. However, the finding of these principles in such a unique setting may indicate Haigh’s (2013) quintessence principles are evident in other TC environments. Originality/value: This is the first research paper that has attempted to test whether Haigh’s (2013) quintessence principles are evident within a given therapeutic community. The research provides empirical evidence for the quintessence principles in a novel TC setting and suggests recommendations for future research.